Tutorat par les pairs pour des étudiants en situation de handicap non visible : la perception des tuteurs - Julien Morand; France Landry; Georgette Goupil; Nicole Bonenfant (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
This paper aims to describe a tutoring program at the University of Quebec in Montreal and to assess the tutors’ appreciations of the program in question. The latter was designed for students-tutees with “invisible handicap” and was intended to improve their study strategies. In this exploratory study, the seven tutors involved describe their motivation, their satisfaction, their role, their perceptions of the actual tutoring training, the activities completed and the challenges encountered. The data was obtained using individual interviews and questionnaires. The results reveal that the tutors seem satisfied with their experience, which in turn appears to have contributed to their professional development. Nevertheless, tutors suggest more supervision activities during the academic session as they came across challenges regarding the tutees’ motivation and managing meetings. The tutors also pointed out issues related to distinguishing learning from study strategies and to the relationships developed with the tutees. The paper closes on recommendations to universities wishing to use tutoring to help students with disabilities.